Relevance of MIS to the management accountant - Abdul Wahab, Mohamed (Penerbit UTM Press, 1990)
This paper poses the challenges that is facing the accounting profession in the information technology era of today and the future. The organizational information that is needed by management must be of value and substance and this requires the use of computer technology by the accountants. Thus, time has come for the accountants to check their functions and roles in the information- based management. The accounting profession like any other is cautious in undertaking drastic changes to their accounting skills and curriculum and this might endanger their existence in the not distant future.